Implementation of Inclusive Education for Students with Special Needs: Study at Madrasah Ibtidaiyah Negeri 1 Bangka Tengah (EDOIS: Journal of Islamic Education, 2024)
Inclusive education is a principle that highlights the significance of ensuring equitable educational opportunities for all students, including those with disabilities or other special requirements. Madrasahs, as Islamic educational institutions, bear a social and religious obligation to offer an all-encompassing educational setting for every child, irrespective of their background. The implementation of inclusive education in madrasahs encompasses multiple facets, such as learners, educators, curriculum, facilities, and infrastructure. This study utilizes a qualitative approach to investigate the implementation of inclusive education for students with special needs at Madrasah Ibtidaiyah Negeri 1 Bangka Tengah. This research aims to provide a detailed description of the implementation of inclusive education at MIN 1 Bangka Tengah. According to the findings, the implementation involved the identification and assessment of children with special needs, as observed by students. Educators still faced challenges in providing care for children with special needs. (c) In terms of the curriculum, the madrasah has not yet created a specific curriculum for students with special needs. (d) The madrasah is still developing its facilities and infrastructure. We have identified five factors that influence the implementation of inclusive education: a) knowledge of inclusive education; b) teacher training; c) teacher attitudes; d) teacher and learner communication; and e) the role of parents.